The Traditional Game of Pata-Pata: Uncovering Physics Concepts and Their Application in School Learning - Anatasija Limba; Elsina S. Tamaela; Juliana Nirahua; Fryan Sopacua; Ledy Manuhutu; Batha N. Akollo; Imanuel V. Huwae; Anastasya Ohoiwutun (Jurnal Penelitian Pendidikan IPA, 2025)
Traditional games are a heritage that has existed since ancient times and has moral and scientific values. Along with the times, traditional games are played rarely by children in Maluku. This study aims to reveal the concept of physics in the traditional game of pata-pata in Wakal Village, Leihitu District, and its implementation to improve mastery of the material at SMA Negeri 18 Central Maluku. This research combines descriptive qualitative method to reveal the concept of physics and descriptive quantitative method to know the improvement of mastery of physics material in the traditional game of Pata-Pata. Data were collected through interviews, document study, test administration and observation of learning implementation. The data were then analyzed using qualitative descriptive and quantitative descriptive data analysis techniques using the N-Gain test. The results of data analysis show that the physics concepts revealed in traditional pata-pata games are bulk modulus, momentum, impulse, collision, sound, Boyle's law, and kinetic energy in the 2013 Curriculum and Merdeka Curriculum. The implementation of pata-pata games in learning the physics concepts of momentum, impulse, collision carried out using the CRT learning approach shows an increase in material mastery. A total of 60% of students experienced an increase in moderate qualifications and 30% of students in low qualifications. The average score of material mastery improvement is 0.21.